Frase Kata Memerintahkan dan Merekomemendasikan dalam Putusan Bawaslu Terkait Pelanggaran Administratif Pemilu - Fauzi Heri; Retna Elyasari (Badan Pengawas Pemilihan Umum, 2019)
Election Supervisory Agency Regulation Number 8 Year 2018 concerning Settlement of Election Administrative Violations has become a guideline for the Election Supervisory Agency in accepting, examining, reviewing, and deciding allegations of Election Administrative Violations. However, there are inconsistencies in the verdict draft stated in Article 55 and Article 56 where there are phrases “ordered” and “recommend”. The General Election Commission must follow up the verdict of the Election Supervisory Agency Election. The verdict of the Election Supervisory Agency contains the phrase “ordered” will not be interpreted otherwise. While the phrase “recommend” can be interpreted differently considering the word recommendation can be interpreted as a suggestion or input. This study is a normative legal research with a qualitative approach. Primary and secondary data were collected through interviews and legislation, general election books whereas the definitions of research variables obtained from dictionaries, encyclopedias and internet media. The results of this study indicates that the phrase “recommend” can be interpreted differently, therefore it has the potential for wrong execution.